Alpha Thalassemia/Mental Retardation Syndrome X-Linked, the Alternative Lengthening of Telomere Phenotype, and Gliomagenesis: Current Understandings and Future Potential - He, Jenny; Mansouri, Alireza; Das, Sunit (Frontiers in Oncology, 2018)
Gliomas are the most common primary malignant brain tumor in humans. Lower grade gliomas are usually less aggressive but many cases eventually progress to a more aggressive secondary glioblastoma (GBM, WHO Grade IV), which has a universally fatal prognosis despite maximal surgical resection and concurrent chemo-radiation. With the identification of molecular markers, however, there is promise for improving diagnostic and therapeutic strategies. One of the key molecular alterations in gliomas is the Alpha Thalassemia/Mental Retardation Syndrome X-linked (ATRX) gene, which is frequently mutated. One third of pediatric GBM cases are also found to have the ATRX mutation and the genetic signatures are different from adult cases. The exact role of ATRX mutations in gliomagenesis, however, is unclear. In this review, we describe the normal cellular function of the ATRX gene product followed by consequences of its dysfunction. Furthermore, its possible association with the alternative lengthening of telomeres (ALT) phenotype is outlined. Lastly, therapeutic options potentiated through a better understanding of ATRX and the ALT phenotype are explored.